Blood Level of 2-arachidonoyl Glycerol (2-AG), Neuropeptide Y and Omentin and Their Correlation with Food Habits in Obese Women: - Rahmanian, Mozhdeh; Lotfi Yaghin, Neda; Alizadeh, Mohammad (Galen Medical Journal, 2020)
Background: Despite growing concern about the increasing global burden of obesity, there are still many uncertainties in understanding the pathogenesis of this disease. This study aimed to investigate the serum levels of 2-arachidonoylglycerol (2-AG), neuropeptide Y (NPY), and omentin, concerning dietary patterns in obese women. Materials and Methods: This case-control study was carried on an equal number of obese (case group) and normal-weight women (n=45 each). Dietary intake was determined based on the food frequency questionnaire. Serum levels of 2-AG, NPY, and omentin were determined using ELISA. Results: The obese group showed significantly higher 2-AG and NPY levels than the controls(P<0.001). There were significant positive correlations between the serum level of 2-AG and calorie intake (r=0.219, P=0.038), carbohydrates (r=0.238, P=0.024), fat (r=0.227, P=0.032), saturated fatty acids (r=0.272, P=0.009), and monounsaturated fatty acids (r=0.265, P=0.012). Conclusion: Our study revealed that dietary patterns, in particular, the type of fatty acids used may influence levels of 2-AG, NPY, and omentin, which all are involved in pathways resulting in obesity.[GMJ.2020;9:e1721]